Numerical analysis of spatial distribution of carbon in methane dry reforming over supported nickel catalyst in a packed bed reactor - Ebrahimi, Parisa (2024)
This study investigates carbon deposition during methane dry reforming over a nickel-based catalyst supported on alumina in a laboratory-scale fixed-bed reactor. Approximately 23.75 g of catalyst was used, and simulations were performed using COMSOL 6.2 software. The reactor was simulated at isothermal wall conditions at four temperatures (650 °C, 750 °C, 850 °C, and 950 °C), with an equimolar CH₄ to CO₂ ratio in the feed. The results showed that while localized carbon deposition density increased with temperature, likely due to a higher local methane decomposition rate, the total amount of carbon deposited was inversely proportional to temperature. This suggests enhanced carbon gasification at higher temperatures. The total carbon deposited was estimated to be around 18 g after 10,000 s of Time on Stream (TOS) at 650 °C. As the temperature increased, the total carbon deposition decreased, although this reduction became negligible beyond 850 °C. Furthermore, the hydrogen to carbon monoxide (H₂/CO) molar ratio peaked at over 1.1 at 650 °C, dropped to approximately 0.76 at 750 °C, and then rose back to 0.97 at 950 °C. Steady-state operation was not achieved due to continuous carbon deposition and accumulation in the reactor. However, in the absence of carbon deposition, steady-state was reached around 100 s after the feed entered, at a velocity of 3 cm/s. Methane conversion reached 97% at 950 °C.